Perkembangan Permukiman Sekitar Wilayah Pertambangan Nikkel Sorowako Kabupaten Luwu Timur - Yoga Pratama; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The existence of a mining company makes less attention to the surrounding local settlements so that it tends to develop into dense and irregular, without a plan in accordance with the spatial pattern of the region. The objectives of this study were (1) to identify the characteristics of settlement development, (2) to analyze the availability of facilities and infrastructure for housing around the mine area and then (3) explain the direction of the concept of settlement development, this research was conducted using qualitative and quantitative analysis, Spatial and comparative, with data collection methods are primary and secondary data, namely surveys and questionnaires from the analysis results obtained that the characteristics of settlement development, seen from housing orientation as much as 59.17% facing the road and 40.83% facing the mine. Conditions for the availability of facilities and infrastructure for housing. The availability of facilities has met the standards but, there still needs to be some additions such as educational facilities, worship and playgrounds / sports while infrastructure, the distribution of clean water has not yet been distributed, the waste water management system is not maximal, the drainage network does not function properly. development, namely environmentally friendly settlements which are more serious on developing access and circulation, namely designing a comfortable and humane pedestrian route and providing complete road facilities and infrastructure services that comply with existing standards.